Adat Upah-Upah setelah Khitanan di Masyarakat Labuhan Bilik Menurut Tokoh Muhammadiyah dan Tokoh Al-Washliyah - Sri Rahmadani; Ahmad Zuhri (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
In Islamic law, tradition/custom is known as Urf, which is ‘something that is considered good and accepted by common sense’. The patterns and differences in the customs of each community in a particular area are caused by the cultural values that underlie the life of the local community. Similarly, the customs adopted by the Labuhan Bilik community in Central Panai Sub-district have a variety of cultures, one of which is the wage-upah custom. This wage-upah custom received two different responses from Islamic mass organisation leaders, namely Muhammadiyah leaders of Panai Tengah Subdistrict and Al-Washliyah leaders of Panai Tengah Subdistrict. This research aims to find out how the implementation, the value contained in the wage-upah custom in the Labuhan Bilik community, how the opinions of Muhammadiyah Leaders and Al-Washliyah Leaders of Central Panai District, as well as which opinion is more relevant in relation to the chronology in Labuhan Bilik Central Panai District. This research uses a comparative empirical sociological research method, qualitative research type with an anthropological approach. The results show that the opinion of Muhammadiyah leaders is more relevant to be applied in Labuhan Bilik, because the wage-upah custom is a form of practice that is a hereditary custom that was not taught by the Prophet, as well as customs that resemble the culture of another religion, namely Hinduism, if you want to show affection or want to give encouragement, just pray directly to Allah swt without going through other intermediaries.